Relationship between Tractor Technology Adoption and Increased Rice Production in Asaki Village, Lambuya Subdistrict, Konawe District - Rinda Maulana; Lukman Yunus; La Ode Arfan Dedu (International journal of technology and education research, 2024)
This research aims to determine the relationship between the adoption of rice production technology and increased rice production in Asaki Village, Lambuya District, Konawe Regency. Determining the research location purposively. The time of the research was carried out in May 2024. The population in this study were farmers in lowland rice farming activities in Asaki Village. The sample was determined using a proportional random sampling technique of 56 people. Data analysis used sperm rank correlation analysis with the help of SPSS. that the use of tractors has a significant relationship with increasing rice production in Asaki Village can be seen from the Spermman rank correlation coefficient value of 0.542 with a significance level of 0.000. This is a significant value smaller than 0.05, meaning that there is a positive correlation between the use of tractors and increased rice production so that Ho is rejected and Ha is accepted. The relationship between the adoption of tractor technology and increasing rice production is in the fairly close category, namely 0.40-0.599, so that the better the use of tractors in cultivating land, the higher the increase in rice production